Difficulties in teaching and learning pronunciation in language focus periods - English 12 and some solutions - Hoàng, Thị Hải Lý (University of Languages and International Studies, 2017)
Chapter 1 presents the theoretical background with definition of pronunciation; the importance of teaching pronunciation; the teacher's and student's roles in teaching pronunciation; the pronunciation components, factors affecting pronunciation learning, and some techniques of teaching pronunciation. Chapter 2, chapter 3 constitutes the body of the study. Chapter 2 is the study of the thesis with an overview on situation of teaching and learning English at Thang Long high school, research questions, and research methodology and data analysis process. Chapter 3 presents data analysis and discussions. Chapter 4 suggests some techniques for teaching pronunciation in “Language Focus Periods” –English 12.